Frequency of Allergic Fungal Rhinosinusitis in Patients of Sinonasal Polyposis (Journal of Fatima Jinnah Medical University, 2018)
Background: Chronic Rhinosinusitis (CRS) is a prevalent disease in Pakistan and allergic fungal rhinosinusitis (AFRS) represents a significant proportion of it. It is an allergic response to fungal elements within the facial sinuses and in the nasal cavity. This study was carried out to determine the frequency of AFRS, in patients of CRS with ethmoidal polyps.Patients and Methods: This cross-sectional study was carried out at ENT Department SGR Hospital, Lahore. The duration was one year (January 01 to Dec. 31, 2016). One hundred and twenty five cases were enrolled in this study. Laboratory investigations included eosinophilic count and total IgE levels. Orbital and Intracranial involvement was ruled out by CT scan. Endoscopically excised polyps and mucin collected from sinuses were sent to the pathologist for histopathology, microscopy and culture.Results: The mean age of the patients was 30 years. There were 67 (53.6%) males and 58 (46.4%) females in the study. In 70 (56%) patient’s microscopy was positive.Conclusion: A significant proportion of patients of CRS with polyps also have AFRS.
Keywords: allergic, fungal rhinosinusitis, sinonasal polyposis.